PENCEGAHAN TINDAK BULLYING MELALUI SOSIALISASI STOP BULLYING DI LINGKUNGAN SD 015 GUNUNG BUNGSU KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Suroyo Suroyo; Adelia Rizka; Aditya Saputra; Arif Maulana; Asrul Ramadani Harahap; Nadira Nurul Atika; Novi Mayani Nababan; Rizki Hizlia Harfani; Siska Ariyanti; Winda Julia; Yabes Maychel (Bajang Institute, 2022)
Prevention of stop bullying in schools can be done, among others, by increasing supervision and providing appropriate sanctions to perpetrators. Another way is to conduct counseling through various means such as socialization or linking material about bullying into learning which will have a positive impact on students' personal development. The purpose of this study was to describe the role of schools in preventing violent acts of bullying in SD Negeri 015 Gunung Bungsu, XIII Koto Kampar District, Kampar Regency. This research method is qualitative with data collection with questionnaire technique. The research participants were elementary school students in grades 3 (three) to 6 (six). The number of participants who took part in the socialization was 64 people. The results of the research obtained by the Kukerta team at the University of Riau were to determine the extent to which elementary school students understood things related to bullying. Schools provide a good response in efforts to prevent bullying in schools by providing rehabilitation if there are victims and providing guidance to perpetrators and evaluating programs to make improvements. Schools can supervise students on their behavior if necessary. Schools are also expected to develop bullying prevention programs by making written regulations.